Agrobiodiversity management for food security [ a critical review - Lenne, Jillian M.; Wood, D. [ (David)] , 1939- (CABI, 2011)
This book aims to build on and extend the wealth of information presented in a previous book, Agrobiodiversity: Characterization, Utilization and Management (Wood and Lenn?, 1999), to show how agrobiodiversity can effectively and efficiently be managed or food security. Chapter 1 revisits the role of agrobiodiversity, while chapter 2 sets the context of the present book by looking at food security. Chapters 3 to 12 critically review many of the past, current and emerging issues affecting agrobiodiversity management for future food security, including: the origins of agrobiodiversity; crop introduction; the utilization of crop diversity for food security; the impact of the introduction of modern varieties on crop diversity; the impact of transgenics on crop diversity; the function and management of crop-associated biodiversity above-and below-ground; agrobiodiversity conservation policy; the International Assessment of Agricultural Knowledge, Science and Technology for Development (IAASTD) process; and agrobiodiversity management for climate change. Chapter 13 offers lessons for policymakers.